THE SOCIAL INCLUSION OF MENTALLY RETARDED THROUGH PHYSICAL EDUCATION ADAPTED (Fiep Bulletin - online, 2014)
By observing the lack and importance in inclusive process through Adapted Physical Education for Mental Disability, has been the study, whose goal is to establish training and foundations of Physical Educators, aware it is vital that clear knowledge of neuroscience and neuroplasticidade, emphasize the need constant demand for neural preserved and operating doors, for integration and significant development of the individual. The inclusion of students with Mental Disabilities, in the Adapted Physical Education, is a perspective and a challenge for the XXI century, ever more firmly in different systems and educational levels. On the adaptive capacity through neuroplasticidade, the learning gap will take its total relevance, even if your system is quite preserved motor of his advances or return, using it as a flag for the professional, giving it the ability to detect before many difficulties the degree of commitment of the brain (SNC) of the individual to work as soon thus developing the student with full security, in view of its features, limitations, capabilities, and helping it in its adaptation in school and the social coexistence.
Keywords: Neuroplasticidade; Adapted Physical Education; Inclusive Education